Psychometric parameters of the attitude/motivation test battery instrument in a mexican environment - Cocca, Michaela; Pérez García, José Alberto; Zamarripa Rivera, Jorge Isabel; Demetriou, Yolanda; Cocca, Armando (Universitat de les Illes Balears Universitat Autónoma de Barcelona, 2017)
In the last decades, research in the field of language learning has focused on understanding the motivational processes beneath people’s interest in studying a second language (L2). For this reason, the attitude/motivation test battery (AMTB) was created in order to assess motivation towards L2. This questionnaire was adapted to the Mexican environment, nevertheless no validation process was carried out. The aim of this study was to assess the validity of the Mexican version of AMTB. A sample of 252 University students filled in the questionnaire. After removing 11 items, the instrument showed high internal validity and suitable factorial structure. The final version of the Mexican AMTB, composed by 43 items distributed into 9 dimensions, can be considered a proper instrument for assessing motivation towards L2 in Mexican students